2020
DOI: 10.3390/coatings10060512
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Environmental Barrier Coatings

Abstract: The global increase in air travel will require commercial vehicles to be more efficient than ever before. Advanced turbine hot section materials are a key technology required to keep fuel consumption and emission to a minimum. Ceramic matrix composites (CMCs) are the most promising material to revolutionize turbine hot section materials because of their excellent high-temperature properties. Rapid surface recession due to volatilization by water vapor is the Achilles heel of CMCs. Environmental barrier coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As a consequence of more than two decades of focused research and development, it has been demonstrated that EBCs are effective tools to protect Si-based substratesespecially SiC/SiC Ceramic Matrix Composites (CMCs)-from the severe pitting corrosion and recession typical of gas turbine applications [2][3][4][5][6][7][8][9][10]. Today, EBC-coated SiC/SiC CMCs are used in high pressure shrouds in 7F gas turbines as well as hot components of the LEAP aircraft engine [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of more than two decades of focused research and development, it has been demonstrated that EBCs are effective tools to protect Si-based substratesespecially SiC/SiC Ceramic Matrix Composites (CMCs)-from the severe pitting corrosion and recession typical of gas turbine applications [2][3][4][5][6][7][8][9][10]. Today, EBC-coated SiC/SiC CMCs are used in high pressure shrouds in 7F gas turbines as well as hot components of the LEAP aircraft engine [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of more than two decades of focused research and development, it has been demonstrated that EBCs are effective tools to protect Si-based substratesespecially SiC/SiC Ceramic Matrix Composites (CMCs)-from the severe pitting corrosion and recession typical of gas turbine applications [2][3][4][5][6][7][8][9][10]. Today, EBC-coated SiC/SiC CMCs are used in high pressure shrouds in 7F gas turbines as well as hot components of the LEAP aircraft engine [7,8]. One of the most critical challenges to tackle is reliability and durability, since failure of EBCs reduces the lifespan of CMC components, with thermal and thermomechanical strains shown to be one of the key contributors to EBC degradation [8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To prevent the deleterious environmental attack of SiC components, environmental barrier coatings (EBCs) were developed to cover the SiC surface. Candidate materials for EBCs should meet a set of requirements [4,[12][13][14], such as hightemperature phase stability, similar thermal expansion coefficient (CTE) to the matrix, chemical compatibility, steam stability, and CMAS corrosion resistance.…”
Section: Introduction mentioning
confidence: 99%
“…To prevent the deleterious environmental attack of SiC components, environmental barrier coatings (EBCs) were developed to cover the SiC surface. The candidate materials for EBC are expected to fulfill a set of requirements [4,[12][13][14], such as high-temperature phase stability, similar thermal expansion coefficient (CTE) to the matrix, chemical compatibility, steam stability, and CMAS corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%